2017
DOI: 10.1159/000481353
|View full text |Cite
|
Sign up to set email alerts
|

Wilms' Tumor Gene 1 (WT1) Peptide Vaccine Therapy for Hematological Malignancies: From CTL Epitope Identification to Recent Progress in Clinical Studies Including a Cure-Oriented Strategy

Abstract: The identification of human Wilms' tumor gene 1 (WT1) protein-derived cytotoxic T lymphocyte (CTL) epitopes and the in vivo efficacy of WT1 peptide-based immunotherapy in a mouse model were reported in 2000. This successful basic research led to clinical studies of a WT1 peptide vaccine, and a positive impact on clinical response was first demonstrated in 2003 in the form of a reduction in blast cells of vaccine-treated patients with myelodysplastic syndromes (MDS). Since then, data on WT1 peptide vaccine-trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 44 publications
(79 reference statements)
1
29
1
Order By: Relevance
“…We previously treated hematopoietic malignancies including leukemia and various kinds of solid tumors with WT1 HLA class I peptide vaccine and reported that the vaccination elicited WT1-specific immunological response, followed by clinical responses without severe adverse effects [29]. One of the most important problems of WT1 vaccination with WT1 HLA class I peptide alone was that WT1-specific CD8 + T cells generally increased at 4–8 weeks post-WT1 vaccination, but afterwards decreased gradually, and their frequency could not be maintained for a long time (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…We previously treated hematopoietic malignancies including leukemia and various kinds of solid tumors with WT1 HLA class I peptide vaccine and reported that the vaccination elicited WT1-specific immunological response, followed by clinical responses without severe adverse effects [29]. One of the most important problems of WT1 vaccination with WT1 HLA class I peptide alone was that WT1-specific CD8 + T cells generally increased at 4–8 weeks post-WT1 vaccination, but afterwards decreased gradually, and their frequency could not be maintained for a long time (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, WT1 was ranked as the top immunotherapy target in cancer by a national cancer institute pilot project for the prioritization of cancer antigens [117]. Numerous clinical studies were carried out implementing peptide vaccination strategies for AML patients in remission after an initial chemotherapy and demonstrated that they are able to induce T-cell responses and are well tolerated with only minor side effects [79,118,119,120]. Furthermore, DC vaccination and adoptive transfer of WT1-specific cytotoxic T cells showed to be auspicious therapeutic options in combination with allogeneic stem cell transplantation in AML patients [121,122].…”
Section: Hla-dependent Antigensmentioning
confidence: 99%
“…Moreover, WT1 has been ranked at the top position in the National Cancer Institute's (NCI) list of cancer antigens with the highest prioritization for vaccine development (221). The use of peptide vaccines against the WT1 antigen showed beneficial therapeutic outcomes in several clinical trials (222, 223).…”
Section: Classification Of Mbpsmentioning
confidence: 99%